Pengaruh Penambahan Titanium Dioksida (TiO2) terhadap Sifat Konduktor dari Polianilin (PANI) - Safira Wulandari; Umar Kalmar Nizar (Departemen Kimia FMIPA UNP, 2023)
This study aims to determine the effect of the addition of TiO2 dopant on the electrical conductivity of polyaniline synthesis using the photopolymerization method and characterization with Fourier Transform Infrared (FTIR) and Diffuse Reflectance UV-Vis (DR UV-Vis). Synthesis of polyaniline was carried out by mixing aniline monomer with Ethylene Glycole Dimetacrylate (EGDMA) as a crosslinker and Dimethoxy Phenylacetophenone (DMPP) as an initiator, and the addition of TiO2 dopant as much as 0.006 g, 0.011 g, 0.016 g, 0.021 g and 0.026 g. The obtained PANI and PANI/ TiO2 were measured for electrical conductivity using the Four Point Probe (FPP), it was found that the optimal electrical conductivity value was 12.60 × 10-3 S/cm which was owned by PANI added with TiO2 of 0.006 g.